From ‘Brain Drain’ to ‘Capital Gain’: Indian Skilled Migration to the UAE - Omar Bortolazzi (15445364) (2023)
This study analyzes the magnitude of emigration of India’s high-skill population in the United Arab Emirates through the exploration of the determinants of emigrant mobility using both an empirical and qualitative approach. It also examines the historical patterns of migration to the GCC region with a focus on the socioeconomic impact of skilled immigration of Indian expatriates in the UAE economy. Furthermore, the chapter attempts to assess the role played by remittances, Foreign Direct Investment (FDI), and knowledge and technology transfers as key economic resources towards the development of the national economy and the potential reversal of the impact of ‘brain drain’. This requires an evaluation of the role played by key stakeholders in the facilitation of migration, providing an alternate outlook on the perceived ‘drain’ and inequality that surrounds the dialog on South-to-North migration. Lastly, the research contributes to the limited literature on transnational entrepreneurs and return and reverse migration, as the most understudied aspect of international migration, to illustrate how the migrant identity is constantly fluid and evolving and ultimately beneficial to both the host and home economy. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_14